Multi‐omics approach in gut and environmental microbiota research under the One Health concept - Anna Kostka; Agnieszka Gruszecka‐Kosowska; Alicia Ruiz‐Rodríguez; Margarita Aguilera (EFSA Journal)
Abstract The One Health concept, although formulated two decades ago, remains challenging to implement. It necessitates the integration of numerous scientific disciplines, diverse techniques and various professional expertise. Furthermore, it often requires the collaboration of different institutions, encompassing both scientific and administrative entities. This concept posits that human health is intrinsically linked to and dependent on the well‐being of animals, plants and the broader environment, while the environment not only sustains life but can also serve as a source of xenobiotics that affect the health‐disease balance. In this context, all components of the potential exposome, encompassing the entirety of factors of various natures that influence health throughout life, must be considered comprehensively. Achieving this holistic understanding typically demands the application of multiple research techniques, known as the multi‐omics approach and the adoption of an integrated method for data analysis. This project endeavoured to utilise such an integrated approach, examining data from diverse origins: human (children stool for gut microbiota analysis) and environmental (groundwater for hyporheic zone microbial analysis), as well as implementing comprehensive informatic tools for data processing. Analysis of stool samples revealed significant differences in gut microbiota composition across various taxonomic levels between normal weight, overweight and obese children. Additionally, a potential link between certain xenobiotics and gut microbiota composition, body weight and overall health status was identified. Analysis of groundwater samples revealed significant differences in hyporheic zone microbial composition at various taxonomic levels based on the sampling location and depth. Key geochemical factors influencing sample diversity were also identified. The promising results obtained not only demonstrate the viability of this methodology but also pave the way for future research initiatives.